(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Recently there is no doubt that the Multiple sclerosis (MS) became a part of primary neurodegenerative disorders. It is a serious neurological disorder which is characterized pathologically by an autoimmune attack directed primarily at myelin, the protective insulation surrounding nerve fibers in the brain and spi- nal cord, and is progressively disabling. It is characterized by the presence of inflammation, neurodegeneration, and demyelinating lesions of white and gray matter. Several evidences suggested that genetics showed factors have a prominent role in the development of multiple sclerosis. The (prevalence) of familial MS is 13% for all MS phenotypes, the risk of MS is 3% in first-degree relatives (siblings 5%, parents 2%, and children, 2%), and only 1% in second and third-degree relatives. EBV is one of the most important risk factors of MS, as a history of EBV infection or triggered acute infectious mononucleosis, stand at an increased risk to develop MS. Elevated serum and CSF anti-EBV antibodies correlate not only to disease onset but also correlate with MS disease activity, and the occurrence of increased EBV loads in patients with MS. The question of whether MS originates in the periphery or in the CNS is still to be comprehensively undetermined, although it is clear that there is a developing immune response. In pathologic specimens, immune cells infiltrate the CNS parenchyma, these cells in association with activated microglia and astrocytes, promote demyelination, oligodendrocyte and axonal injury, the demyelinating lesions of MS, called plaques, appear as indurated areas—hence the term sclerosis. Examination of the demyelinating lesions in the spinal cord and brain of patients with MS shows myelin loss, destruction of oligodendrocytes, and reactive astrogliosis, often with relative sparing of the axon cylinder. In some MS patients, however, the axon is also aggressively destroyed. The clinical presentation of MS is heterogeneous and depends on the loca- tion of demyelinating lesions within the CNS. Symptoms of a clinical attack typically show an acute or sub-acute onset, worsen over days or weeks, reach a peak severity within 2–3 weeks and remit completely or to a variable degree, ranging from minimal resolution to complete recovery normally 2–4 weeks after reaching maximum deficit.